From Development to Securitization: How Terrorism Transformed CPEC and Pakistan China Relations (2015–2024) - Imran Ali; Dr. Shahzad Akhtar (Corresponding Author); Ms. Shehneel Khalid (Journal of Religion and Society, 2025)
This article examines how terrorism has reshaped the China–Pakistan Economic Corridor (CPEC) and bilateral relations between 2015 and 2024. Using securitization theory, it adopts a qualitative case-study design and content analysis of secondary sources to explore attack patterns and policy responses. Findings reveal that repeated assaults on CPEC projects and Chinese nationals increased costs, delayed timelines, and institutionalized counterterrorism within the partnership’s operational framework. Measures such as the Special Security Division, stricter movement protocols, and a security sub-group under the Joint Cooperation Committee illustrate how CPEC evolved from a development-first initiative into a security-governance model. Conceptually, the study frames terrorism as a “dual-force variable,” simultaneously constraining economic progress while reinforcing strategic alignment through institutionalized security cooperation. By highlighting this dual effect, the article provides one of the first systematic analyses of terrorism’s governance impact on CPEC and concludes that its long-term sustainability depends on balancing militarized protection with inclusive governance and community participation, offering insights for other Belt and Road corridors in fragile environment. Keywords: CPEC, Pakistan-China relations, terrorism, securitization theory, counterterrorism cooperation